ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI IMPOR BERAS INDONESIA - Dwidjono Hadi Darwanto; Endang Siti Rahayu (Universitas Sebelas Maret, 2008)
Most of all developing countries including Indonesia gave serious enough attention to overcome incursion import and also low import price problem. In many cases, low import product price into a state will have several bad effects to agriculture industry, rural development and employment. This research aims are (1) to know and analyze factors influence to rice import and (2) to know elasticity of rice import variable. The research use time series data, with secondary data type starting 1969-2004 year which collected from various archives or publication from Department of Agriculture, Statistical Bureau Center, BULOG, FAO, IRRI and relevant publication with this research. Analysis method used by econometric with OLS (Ordinary Least Square). Because of used time series data for the estimation, so will be test stationer of variable in data analysis (Koutsoyiannis, 1978). And than testing for degree of integration and to see long-range and short-range model used ECM Engle-Granger, 1997 (Insukindro, 2002).Conclusion of the research are (1) factors influence rice import is previous year import factor in short-range and long-range, despitefully rice import on a long term influenced also by earnings, (2) elasticity of previous year rice import in short-range 0,77 (inelastic) and on a long-range 0,40 (inelastic), while earnings elasticity is 13,5 (elastic). Research implication to depress rice import is substitution rice with higher value level of commodity.